Identifikasi Atribut Kepuasan Mahasiswa Terhadap Layanan Sistem Pembelajaran Online Menggunakan Metode WebQual dan Kano - Dafid; Dorie Pandora Kesuma (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
This study aimed to measure the level of user satisfaction, in this case are the students of STMIK XYZ about online learning system service by conducting identification processof user satisfaction attributes based on WebQual method and Kano Model. WebQual method provides measurement factors of user satisfaction and then measured by using Kano Model. The population in this study was students at STMIK XYZ. The results showed that of the 22 attributes of WebQual were analyzed by Kano Model showed 19 attributes entered into the One-dimensional categories, 2 attributes for the Attractive categories and 1 attribute entered into the Indifferent category.